Development without employment - MEIER, G.M. (PSL Quarterly Review, 2014)
<!--[if gte mso 9]> 72 1024x768 <![endif]--> One of the most perplexing - and serious - problems now confronting many of the less developed countries is their growing level of urban unemployment. A number of studies have emphasized the broad dimensions of the problem: industrial employment has lagged behind growth in industrial output, behind growth of the urban population, and even behind the general growth rate of population. The evidence suggests that the Keynesian theory of unemployment does not fit these countries. Even more, it indicates that development plans have failed to achieve their objective of providing a substantial growth of employment opportunities in the modern industrial urban sector. The present work examines the major reasons why development plans have generally been unsuccessful in solving the unemployment problem, before considering possible correctives for the situation of increasing unemployment. JEL: E24, O11 <!--[if gte mso 9]> Normal 0 14 <![endif]--><!--[if gte mso 10]> <![endif]-->